Effectiveness and safety of the direct oral anticoagulant in acute distal deep vein thrombosis: From the prospective multicenter observational study, J'xactly, in Japan. (February 2023) - Mo, Makoto; Fukuda, Ikuo; Nakamura, Mashio; Yamada, Norikazu; Takayama, Morimasa; Maeda, Hideaki; Yamashita, Takeshi; Ikeda, Takanori; Yamazaki, Tsutomu; Okumura, Yasuo; Hirayama, Atsushi; ,
Objectives: We assessed the effectiveness and safety of rivaroxaban in patients with isolated distal deep vein thrombosis (IDDVT). Methods: Symptomatic venous thromboembolism (VTE) and major bleeding were assessed. Results: Of 1016 patients with acute symptomatic/asymptomatic DVT and/or pulmonary embolism treated with rivaroxaban, 288 had IDDVT and 294 had proximal DVT (pDVT). The IDDVT group had fewer patients on the higher rivaroxaban dose (30 mg/day) (42.7% vs. 66.0%) and a shorter treatment duration (135.5 vs 369.5 days) than the pDVT group. VTE recurrence occurred in 14 and 11 patients with IDDVT and pDVT, respectively (2.89% vs. 2.29% per patient-year; p = 0.534). Major bleeding was less frequent in the IDDVT group (1.55% vs. 4.53% per patient-year; p = 0.044). Comparable effectiveness and safety were observed with 15 and 30 mg/day rivaroxaban in the IDDVT group. Conclusions: Short-term, low-dose rivaroxaban seems safe and effective for IDDVT treatment.